"Tygodni Powszechny": w poszukiwaniu mądrości - Pera, Marcin (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
“Tygodnik Powszechny” is one of the oldest and the most merited Polish newspapers. It went through at least two periods while it served as an oppositional newspaper. This oppositional and intelligent character gave the paper a specific status in the world of Polish media. At the same time, it was difficult for “Tygodnik Powszechny” to undergo the change required by contemporary free market. What is more, taking “Tygodnik Powszechny” as an example, one could observe the vast majority of changes which influenced Polish media in the course of the last several days. A combination of rich history, deeply rooted catholic tradition and modern trends create a completely new image of Cracowian newspaper